Comparative studies of the oxidation of MoSi2 based materials: High-temperature oxidation (1000–1600 ° C). (December 2017) - Samadzadeh, M.; Oprea, C.; Karimi Sharif, H.; Troczynski, T.
Abstract: Molybdenum disilicide (MoSi2 ) exhibits good oxidation resistance above 1000 ° C due to the formation of a continuous SiO2 layer (or alumina layer for the materials doped with aluminum). However, during high-temperature service, the protective layer on MoSi2 -based materials could be damaged, e.g. due to erosion, volatilization, and micro-cracks in thermal cycling, and due to exposure to reducing atmospheres. Consequently, such damaged MoSi2 can rapidly re-oxidize. In this study, the oxidation characteristics of MoSi2 based materials were investigated in air, with the pre-oxidized protective layer removed to simulate such surface damage. Five different, commercially available, MoSi2 based heating elements, i.e. Kanthal Super (labelled by the manufacturer as KS-1700, KS-1800, KS-1900, KS-ER and KS-HT) were exposed to 1000–1600 ° C isothermally, for 2 to 144 h, and their mass changes determined. Scanning Electron Microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) analyzed the microstructure, chemical composition and phase composition of the oxidized samples. The constitution of the oxide scale and oxidation reaction activation energy of each of the MoSi2 -based materials were determined. It was found that the oxidation behavior of these MoSi2 based materials strongly depended on their chemical and phase composition, in addition to the exposure time and temperature. A dense barrier alumina film (∼1.5 μm thick at 1000 ° C to ∼50 μm thick at 1500 ° C for exposures up to 144 h) formed on KS-ER samples and a dense glassy SiO2 film (∼3 μm thick at 1000 ° C to ∼50 μm thick at 1600 ° C for exposures up to 144 h) formed on the other types of samples. Highlights: The constitution of the oxide scale and oxidation reaction activation energy of each of the MoSi2 -based materials were determined. (Mo, W)Si2 materials, especially KS-HT, showed better oxidation resistance than Mo (Si, Al)2 and MoSi2 at 1000–1600 ° C. Massive disintegration and mass loss were observed in the samples of KS-ER at 1600 ° C. No sign of bubbling of the silica scale was detected; therefore, MoO3 did not form beneath the scale. Spallation of the SiO2 scale occurred only at 1600 ° C for KS-1700.